2012
DOI: 10.1097/sla.0b013e318251610f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prophylactic Transpapillary Pancreatic Stent Insertion on Clinically Significant Leak Rate Following Distal Pancreatectomy

Abstract: The results from this trial show that prophylactic pancreatic stenting does not reduce PF when performing a standardized resection of the body and tail of the pancreas. The trial was registered at clinicaltrials.gov NCT00500968.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 27 publications
(23 reference statements)
0
56
0
Order By: Relevance
“…Hashimoto et al [13] reviewed 223 consecutive cases of DP and reported that preoperative endoscopic intervention at Wirsung's duct, including endoscopic stent placement, significantly reduced the risk of POPF. However, a prospective RCT in a single institution in Sweden failed to show a prophylactic effect of pancreatic stent insertion against POPF [82]. In this RCT, clinically significant POPF and intra-abdominal abscess were more frequent in patients with stents than in patients without stents; however, this difference was not statistically significant.…”
Section: Pancreatic Stentingmentioning
confidence: 55%
“…Hashimoto et al [13] reviewed 223 consecutive cases of DP and reported that preoperative endoscopic intervention at Wirsung's duct, including endoscopic stent placement, significantly reduced the risk of POPF. However, a prospective RCT in a single institution in Sweden failed to show a prophylactic effect of pancreatic stent insertion against POPF [82]. In this RCT, clinically significant POPF and intra-abdominal abscess were more frequent in patients with stents than in patients without stents; however, this difference was not statistically significant.…”
Section: Pancreatic Stentingmentioning
confidence: 55%
“…Several operative procedures for these tumors have been developed over the past 20 years, including the use of spleen preservation (1) and laparoscopic surgery (2). However, the incidence of the most common and most serious postoperative complication after DP, postoperative pancreatic fistula (PF), was not found to be improved in several clinical prospective trials (3)(4)(5). It is apparent that a radical change in postoperative management is necessary to prevent PF after DP.…”
Section: Introductionmentioning
confidence: 99%
“…That trial failed to show a benefit of preoperative stenting of the pancreatic duct and in fact demonstrated a trend toward a significantly increased rate of pancreatic fistula among patients with preoperative stent placement [16]. An example that highlights the significant difficulty in obtaining robust best practice standards in this area comes from a similar controversy in pancreaticoduodenectomy.…”
Section: Role Of Pancreatic Stentingmentioning
confidence: 95%